Performance evaluation of a communication network - Ncube, Ariage T (Department of Electrical Engineering, 2016)
This work uses a simulation package to analyze the performance of a specific X.25 Value Added Communication Network (VAN), comprising a Network Administrator and a cluster of Network Concentrators (NCs). Detailed models of the network elements are developed, and system performance is analyzed in terms of network response time for the terminal users communicating across the network, identification of areas of bottlenecks in the NC system, and NC system throughput. The througput parameter is represented by the percentage of the output traffic to the load offered from the network of terminals. The performance of the Network Administrator system is also modeled, focusing particularly on the automatic restoration of service to failed NCs through downloading of operating software sets over the X.25 network. The final part consists of a model of a modification of the network manager components of the network as proposed in the DM upgrade project. In this section, NC loading time is again the desired performance indicator. It is shown that there is no noticeable improvement in this parameter between the original system and the proposed upgrade, both systems having a minimum loading time of about 3.5 to 6 minutes for a small network.